(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the Mongol invasion of Central Asia and the subsequent struggle against their oppression. It explores the political situation prior to the invasion, the causes and stages of the Mongol military campaigns, and the devastating impact of their rule on the region’s population, economy, and cultural life. Special attention is given to the resistance movements, particularly the role of Jalal ad-Din Manguberdi, who became a symbol of national courage and defiance. The study also analyzes the long-term consequences of Mongol domination and highlights the historical lessons and significance of the struggle for freedom.